Optimalisasi Tata Kelola Keuangan Diri di Era Digital: Strategi dan Implementasi - Benardi Benardi; Dadang Irawan; Arogya Christian Abhi Thama (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Personal financial management in the digital era is a crucial aspect affecting the economic well-being of individuals and families. Amidst global economic dynamics, financial technology development, and increasing daily needs, the ability to manage finances effectively has become increasingly essential. This research explores strategies and implementations for optimizing personal financial management in the digital era, focusing on financial literacy, financial technology use, and healthy financial habits. The research results indicate that financial literacy in Indonesia is still low, with a score of 57 below the global average (60), and the national financial literacy rate only reached 49.68% in 2022. On the other hand, financial inclusion has reached 85.10%, highlighting a gap between access to and understanding of financial matters. Financial technology (fintech) offers easy access but also increases the risk of debt without mature planning. A holistic approach to financial management includes financial literacy, forming healthy financial habits, and using technology to support financial management. This webinar aims to educate and promote implementing adaptive, responsive, and effective personal financial management in facing modern financial challenges.